The Name Māra in the 16–17th century Latvian texts and in the „Historical Dictionary of Latvian”: Proper names and common nouns - Siliņa-Piņķe, Renāte; Trumpa, Anta (Baltistica, 2017)
Marija and its Latvianized form Māra (including the diminutive Māriņa) is one of the most frequently observed proper names in the 16–17th century Latvian texts. This article analyzes the forms of this name found in the “Corpus of Early Latvian Texts” (Latviešu valodas seno tekstu korpuss), which were later included in three separate entries in the „Historical Dictionary of Latvian” (Latviešu valodas vēsturiskā vārdnīca; henceforth LVVV): (1) Marija, Mārija, (2) Mara, Māra, Maŗa, Māŗa, and (3) Mariņa, Māriņa. Since most of the 16–17th century Latvian texts are of religious nature, these words are mostly used in a Christian context, and their meaning is ‘[Saint] Mary’. An interesting exception is an example from a 17th century dictionary – the popular name Kāposta Māriņa of a church holiday, and the example of a song from the manuscript of Christoph Fürecker’s dictionary, which allow to add the words ‘Māra’ and ‘Māriņa’ to the respective entries. In Latvian, just like in many other languages, the name denoting Saint Mary is a rather widespread component of plant names – most probably because in the Catholic tradition the image of Saint Mary has long been associated with protection and healing. LVVV contains such entries as mārarutks, māŗarutka and mārapīne. However, these are not derived from a personal name, but from phonologically similar first components of German compound words. These hybrid words, partial German borrowings, at some points in the history of written Latvian were interpreted as related to Mārja / Māŗa / Māra, as a result of folk etymology, and used as collocations. In LVVV, these collocations do not have separate entries, but are included in the entry Mara, Māra, Maŗa, Māŗa. However, the 17th century compounds mārarutks, māŗarutka analyzed in this article are not really a case of folk etymology and are thus not related to a personal name, while the compound mārapīne with its variants has a more tenacious semantic link with the respective name.